2020
DOI: 10.3390/ijms21186507
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Cells Derived from Induced Pluripotent Stem (iPS) Cells Suppress or Activate T Cells via Costimulatory Signals

Abstract: Human retinal pigment epithelial (RPE) cells derived from induced pluripotent stem (iPS) cells have immunosuppressive properties. However, RPE cells are also known as immunogenic cells, and they have major histocompatibility complex expression and produce inflammatory proteins, and thus experience immune rejection after transplantation. In this study, to confirm the immunological properties of IPS-RPE cells, we examined whether human RPE cells derived from iPS cells could suppress or stimulate inflammatory T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(84 reference statements)
0
5
0
1
Order By: Relevance
“…Due to the ability of fRPE cells to express HLA-DR molecules following IFN-γ exposure, we focused on the CD4+ T cell subset ( Supplementary Figure S2A ) and analyzed their proliferation and cytokine production. It has been recently shown that cultured RPE cells can suppress or activate T cells in vitro [ 41 ]. Therefore, we first co-cultured fRPE cells with PBMCs in the absence of other exogenous stimuli to test their ability to promote a T cell response.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the ability of fRPE cells to express HLA-DR molecules following IFN-γ exposure, we focused on the CD4+ T cell subset ( Supplementary Figure S2A ) and analyzed their proliferation and cytokine production. It has been recently shown that cultured RPE cells can suppress or activate T cells in vitro [ 41 ]. Therefore, we first co-cultured fRPE cells with PBMCs in the absence of other exogenous stimuli to test their ability to promote a T cell response.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the immunogenic nature of RPE cells, strategies aimed at mitigating intraocular inflammation following transplantation need to be considered [ 28 ]. Previous reports have shown that ROCK inhibitors exert immunosuppressive effects, including suppressing allogeneic immune responses and graft-versus-host disease [ [29] , [30] , [31] ] [ [29] , [30] , [31] ] [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our in vitro assays, MHC class II on RPE cells was downregulated by Y-27632, suggesting that immune rejection of a graft would be reduced by Y-27632. Since RPE cells exhibit immunogenic properties [ 29 ], we have to consider how to reduce intraocular inflammation after transplantation. To test the effect of Y-27632 against immune rejection, further in vivo experiments will be required to see whether administration of Y-27632 during transplantation allows for fewer or no immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%